2014
DOI: 10.1016/j.ijpara.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression in the protozoan parasite Entamoeba invadens: identification of core promoter elements and promoters with stage-specific expression patterns

Abstract: Developmental switching between life-cycle stages is a common feature among many pathogenic organisms. Entamoeba histolytica is an important human pathogen and is a leading parasitic cause of death globally. During its life cycle, Entamoeba converts between cysts (essential for disease transmission) and trophozoites (responsible for tissue invasion). Despite being central to its biology, the triggers that are involved in the developmental pathways of this parasite are not well understood. In order to define th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
(92 reference statements)
1
16
0
Order By: Relevance
“…To find out whether the ERM motif is functional in the context of a full-length promoter, we used a luciferase reporter construct driven by a cyst-specific promoter that contains the WT-ERM. We have previously demonstrated that this construct increases expression during encystation ( Manna et al, 2014 ). A Mut-3-ERM-Luciferase construct was generated by changing CA to TG at fourth and fifth positions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…To find out whether the ERM motif is functional in the context of a full-length promoter, we used a luciferase reporter construct driven by a cyst-specific promoter that contains the WT-ERM. We have previously demonstrated that this construct increases expression during encystation ( Manna et al, 2014 ). A Mut-3-ERM-Luciferase construct was generated by changing CA to TG at fourth and fifth positions.…”
Section: Resultsmentioning
confidence: 95%
“…All the oligonucleotides used in EMSA are listed in Figure 1—source data 2 . The cyst-specific promoter construct, C4, has a WT-ERM, a luciferase reporter gene and 3’ regulatory region ( Manna et al, 2014 ). ERM was mutated by changing CA to TG at fourth and fifth position by site-directed mutagenesis kit (Agilent-QuikChange Lightning).…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that the increase in HC patches was an early event during encystation. It could be related to up-or down regulation of stage specific genes which takes place in cells committed for encystation [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we unfortunately did not find genes that could function as stage-specific triggers. However, we know that trigger silencing is dependent on promoter activity (20), and thus, the recent identification of stage-specific promoters in E. invadens means that we can use this approach to develop stage-specific trigger silencing (57). Expressing the trigger under the stage-regulated promoters will help regulate the exact stage at which transcription occurs and at which small RNAs can be generated.…”
Section: Discussionmentioning
confidence: 99%